Continuing Higher Education and Lifelong Learning An international comparative study on structures, organisation and provisions - Knust, Michaela; Hanft, Anke.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
This comparative survey was conducted in 2006 and shows the structure, organisation and types of provisions of continuing higher education in six countries (in alphabetical order): Austria, Finland, France, Germany, the United Kingdom and the United States of America. In addition to that, other "important players" in the field of lifelong learning are included, such as corporate universities and research associations. All country studies analyse the functions and restraints of continuing higher education. This is done by analysing a) the relevant framework conditions in each country, b) the management (organisational structures, financial management, marketing, quality assurance, programme portfolios, learn settings etc.) and c) the types of provisions (face-to-face lessons, online learning, blended-learning; admission to courses; accreditation of prior learning; credit points etc.). The summary of the country studies finally shows a survey of the individual situations and displays the similarities and differences. It draws conclusions for the activities of higher education institutions as lifelong learning institutions.
Continuing Higher Education in a State of Flux: An International Comparison of the Role and Organisation of Continuing Higher Education -- Design of the International Comparative Study -- Comparative Overview of Study Results -- Continuing Higher Education in Germany -- Continuing Higher Education in Finland -- Continuing Higher Education in France -- Continuing Higher Education in the United Kingdom -- Continuing Higher Education in Austria -- Continuing Higher Education in the United States of America (USA) -- Corporate Universities and Research Associations as Players in Continuing Higher Education.
Keywords: Education; School management and organization; School administration; Educational policy; ducation and state; Higher education; Lifelong learning; Adult education; Education; Higher Education; Lifelong Learning/Adult Education; Educational Policy and Politics; Administration, Organization and Leadership; Electronic books